2016
DOI: 10.1292/jvms.15-0706
|View full text |Cite
|
Sign up to set email alerts
|

The cell wall component lipoteichoic acid of <i>Staphylococcus aureus</i> induces chemokine gene expression in bovine mammary epithelial cells

Abstract: Staphylococcus aureus (SA) is a major cause of bovine mastitis, but its pathogenic mechanism remains poorly understood. To evaluate the role of lipoteichoic acid (LTA) in the immune or inflammatory response of SA mastitis, we investigated the gene expression profile in bovine mammary epithelial cells stimulated with LTA alone or with formalin-killed SA (FKSA) using cap analysis of gene expression. Seven common differentially expressed genes related to immune or inflammatory mediators were up-regulated under bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
1
21
1
Order By: Relevance
“…PGN and LTA are the major cell wall lysis components [29]. They can stimulate the bovine mammary gland to produce proinflammatory factors and then induce mastitis and reduce lactation [7,[30][31][32]. However, their proinflammatory activity is weaker than that of LPS [2][3][4], a cell wall lysis component of gram-negative bacteria like E. coli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGN and LTA are the major cell wall lysis components [29]. They can stimulate the bovine mammary gland to produce proinflammatory factors and then induce mastitis and reduce lactation [7,[30][31][32]. However, their proinflammatory activity is weaker than that of LPS [2][3][4], a cell wall lysis component of gram-negative bacteria like E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…The weak and persistent proinflammatory activity of LTA and PGN mainly causes subclinical and chronic mastitis [2][3][4] which is difficult to detect and cure. Previous studies have reported the effects of LTA and LTA + PGN on gene expression profiling of bovine mammary epithelial cells, and mainly focused on the proinflammatory activity of PGN and LTA [5][6][7]. However, the epigenetic modification mechanisms of the inflammation induced by PGN and LTA remain poorly understood, and the direct effects of PGN and LTA, alone or combined, on lactation of bovine mammary epithelial cells and the inherent epigenetic mechanisms receive little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Prototheca zopfii GT-II induced more IL-8 mRNA in bMECs compared to GT-I-inoculated or uninfected cells. Increased levels of IL-8 mRNA in murine MECs and bovine MECs induced by P. zopfii GT-II demonstrated that mammary epithelial cells are an important source of IL-8 and that this chemokine is key during protothecal mastitis, perhaps by recruiting leukocytes, as demonstrated by its chemoattractant role in Staphylococcus aureus infection in bMECs 35,36 . Depolarization of mitochondrial transmembrane (ΔΨm) causes the release of cytochrome-c, which may initiate caspase cascade.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus (BM1006 [ 16 ], SA003 [ 17 ] and JE2 [ 18 ]), S. epidermidis (ATCC14990) [ 19 ], Bacillus atrophaeus (ATCC9372) [ 20 ], and E. coli (JM109) [ 21 ] were used in the present study. BM1006 was isolated from the bulk milk of dairy cattle, and SA003 originated from the milk of dairy cattle suffering from mastitis.…”
Section: Methodsmentioning
confidence: 99%